Encapsulation of commercial and emerging solar cells with focus on perovskite solar cells - Aitola Kerttu; Gava Sonai Gabriela; Markkanen Magnus; Kaschuk Joice Jaqueline; Hou Xuelan; Miettunen Kati; Lund Peter D (Elsevier Ltd, 2022)
Solar cell encapsulation literature is reviewed broadly in this paper. Commercial solar cells, such as silicon and thin film solar cells, are typically encapsulated with ethylene vinyl acetate polymer (EVA) layer and rigid layers (usually glass) and edge sealants. In our paper, we cover the encapsulation materials and methods of some emerging solar cell types, that is, those of the organic solar cells, the dye-sensitized solar cells and the perovskite solar cells, and we focus on the latter of the three as the newest contender in the solar cell arena. The PSC encapsulation literature is summarized in a comprehensive table we hope the reader may use as a “handbook” when designing encapsulation and long-term stability experiments. Some additional functionalities included in encapsulants are also discussed in our paper, e.g. improving the encapsulants’ optical properties and manufacturing them sustainably from biobased materials.